Which models are needed for Pinus pinea forests? A review on current state and potential use - Calama R.; Manso R.; Gordo J.; Montero G.; Mutke S.; Piqué M.; Vazquez-Piqué J.; Pardos M. (Mediterranean pine nuts from forests and plantations, 2017)
We aim to make a critical review of the current state of the art of modelling in Mediterranean stone pine forests, focusing on the stakeholders and end-users criticisms and points of views. To do this we first present an exhaustive review and analysis of the currently available literature on the topic, in order to detect gaps in knowledge. In a second part of the study, we analyze whether the stakeholders involved in stone pine managements make use of the existing models. We also analyze which are the characteristics and requirements that the potential end-users demand to the models. Our results show an extraordinary development in the modelling activity for the species, identifying more than 109 scientific references, of which 72 are published in JCR® journals, although some gaps are observed. Despite this large availability of models, potential end-users of the models currently don´t make an in-depth use of these tools, since in many occasions their demands are not met by the expected outputs.
2. International Meeting on Mediterranean Stone Pine for Agroforestry : AgroPine2016, 2016/05/18-20, Oeiras (Portugal)